The preparatory plan to prevent transmission of the COVID-19 for Malaysian institutes of higher learning - Ahmad H.Osman, Rahmah (2020)
The Ministry of Education has been kept up to date on the spread of the COVID-19 infection, based on reports from the Ministry of Health Malaysia (MOH) and the World Health Organization (WHO). The Ministry is aware of the concerns of the campus community as well as the potential and risk of transmission of the virus to University campuses. Hence, The Ministry has taken proactive steps including the engagement with the Majlis Kesihatan Universiti Awam Malaysia (MAKESUM) to improve our readiness to curb the spread and address the potential dangers of the virus. All Institutes of Higher Learning should take proactive steps to ensure the campus safety, resident’s wellbeing and business continuity. All campus residents are also reminded to practice preventive measures as recommended by Ministry of Health to ensure that the University’s operations are not affected. The University must always comply with the guidelines set by the Ministry and maintain in close contact with Ministry of Health to prevent the spread of COVID-19 infections. The University must keep up to date with any updates made on any issues related to the infection to ensure the safety and well-being of the campus residents.